2021
DOI: 10.1155/2021/6640527
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differences in ECG Characteristics for Different Types of Drivers under Anxiety

Abstract: Anxiety is a complex emotion characterized by an unpleasant feeling of tension when people anticipate a threat or negative consequence. It is regarded as a comprehensive reflection of human thought processes, physiological arousal, and external stimuli. The actual state of emotion can be represented objectively by human physiological signals. This study aims to analyze the differences of ECG (electrocardiogram) characteristics for various types of drivers under anxiety. We used several methods to induce driver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Wang et al selected the time-frequency domain, waveform and non-linear characteristics of ECG signals to recognize drivers' anxiety and calmness based on BP network and Dempster-Shafer evidence [16]. Guo et al found that there were significant differences between drivers with different gender, age and driving experience in terms of ECG characteristics in time and frequency domain as well as waveform under anxiety [17].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al selected the time-frequency domain, waveform and non-linear characteristics of ECG signals to recognize drivers' anxiety and calmness based on BP network and Dempster-Shafer evidence [16]. Guo et al found that there were significant differences between drivers with different gender, age and driving experience in terms of ECG characteristics in time and frequency domain as well as waveform under anxiety [17].…”
Section: Introductionmentioning
confidence: 99%
“…Using a diferent indicator, the velocity of instantaneous maximum pupil size for drivers' visual workloads, Jiao et al found that in underwater urban tunnels, owing to better lighting, the time drivers take to adapt to brightness and darkness is shorter, and the driving experience is more comfortable than that in regular tunnels [8]. Guo et al studied the infuence of diferent emotion-inducing materials on drivers' visual workload, and heart rate (HR) was used to indicate the drivers' visual workload [9]. Moreover, Zhu et al adopted HRV as an indicator of drivers' visual workload to study the infuence of familiarity with the road environment on drivers' visual loads and found that drivers familiar with the road in the experiment had signifcantly lower visual loads than those who were not familiar with the road [10].…”
Section: Introductionmentioning
confidence: 99%